We are given the equation of a curve;
![2x^2-4x^{(3)/(2)}-(8)/(x)-1](https://img.qammunity.org/2023/formulas/mathematics/college/3iz2vp20ywlotoqybeedn4oj26mwxamz66.png)
To solve this we begin by taking the derivative of this curve. Note that the slope of this curve is its first derivative.
We now have;
![\begin{gathered} (d)/(dx)(2x^2-4x^{(3)/(2)}-(8)/(x)-1 \\ =4x-6x^{(1)/(2)}-(8)/(x^2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3bqjiooujxibioxcnd7unyz8qmpl7tppj9.png)
At this point we should note that the slope (gradient) is the value of this first derivative when x = 4.
We can now plug in this value and we'll have;
![\begin{gathered} f^(\prime)(x)=4x-6x^{(1)/(2)}-(8)/(x^2) \\ At\text{ } \\ x=4,\text{ we would have;} \\ f^(\prime)(4)=4(4)-6(4)^{(1)/(2)}-(8)/(4^2) \\ f^(\prime)(4)=16-6(2)-(8)/(16) \\ f^(\prime)(4)=16-12-(1)/(2) \\ f^(\prime)(4)=3(1)/(2) \\ OR \\ f^(\prime)(4)=(7)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pyzcqskfptow6jajdedl43f0czl139k26s.png)
Now we can see the slope of the curve. The slope of the normal line perpendicular to the tangent of the curve is a negative inverse of this.
The negative inverse of 7/2 would be;
![\begin{gathered} \text{Gradient}=(7)/(2) \\ \text{Gradient of perpendicular}=-(2)/(7) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/px9o3lqubw8mfet5c941p04b3rwgj4fbxt.png)
Now to use this value to derive the equation in the form
![ax+by+c=0](https://img.qammunity.org/2023/formulas/mathematics/college/owc0qd2nt1d9qswcch8nh8gjwxzqwvdv3x.png)
We start by expresing this in the form;
![y=mx+b](https://img.qammunity.org/2023/formulas/mathematics/high-school/smsb8cbft03lwblmi49nf2l6jby2ofxzws.png)
We now have;
![y=-(2x)/(7)+b](https://img.qammunity.org/2023/formulas/mathematics/college/q62dy21sn5thtks6u1zntuwt2lrwmlzv3r.png)
We can convert this to the standard form as indicated earlier;
![\begin{gathered} From\text{ the original equation; when} \\ x=4 \\ y=2(4)^2-4(4)^{(3)/(2)}-(8)/(4)-1 \\ y=32-4(8)-2-1 \\ y=32-32-2-1 \\ y=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mlire6ien9suotoj8dsmi3xeygunup5kgy.png)
With the points
![(4,-3)](https://img.qammunity.org/2023/formulas/mathematics/college/2v9y5zujy3p7rctu71tdxyd7m0nkk5vv3a.png)
We now have, the equation;
![\begin{gathered} y=mx+b \\ -3=-(2(4))/(7)+b \\ -3=-(8)/(7)+b \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hfefbb2ffc1kbfi73t69q4lp8n1otvlcwn.png)
We now collect like terms;
![\begin{gathered} b=(8)/(7)-3 \\ b=-(13)/(7) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lxj5n1gvlcfkvne6bw4zqm5f1ohyw3cgk6.png)
We now have the y-intercept as calculated above.
We can now write up our equation is the standard form as indicated from the beginning;
![\begin{gathered} ax+by+c=0 \\ (x,y)=(4,-3) \\ c=-(13)/(7) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5q6jl8i162ui4n4hw1kyxe50p048pkm19u.png)
![\begin{gathered} 4a+(-3)b+(-(13)/(7))=0 \\ 4a-3b-(13)/(7)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rj5h9epf27bsnpxjf257ey6ppq3m4pstlm.png)
Note that A, B and C must be integers. Therefore, we multiply all through by 7;
ANSWER:
![28a-21b-13=0](https://img.qammunity.org/2023/formulas/mathematics/college/5cvarifth14swljbtxg91ilemegusxgjdx.png)